Humor, crisis y crítica en la poesía tardía de Pablo Neruda - Sara-de La Vaissière, Marie-Laure (Kwartalnik Neofilologiczny, 2023)
Since 1950, nerudian poetry explores humor’s expresive shades as a new aesthetic strategy to face personal and political turmoils. If such humor can be critical, it though becomes both a bitter miror, a stronghold and a releasing comfort.
Keywords: Neruda; humor; crisis; dictature; resistance